2020
DOI: 10.3389/fspor.2020.00011
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Anterior Cruciate Ligament Injuries in Competitive Adolescent Alpine Skiers

Abstract: Anterior cruciate ligament (ACL) injury is one of the most serious injuries among Swedish alpine ski high school students. An ACL injury forces the skier to stop skiing for several months, and some skiers even have to give up their skiing career. Therefore, an ACL injury prevention program might play an important role for alpine skiers. In the present study ski high school students have been followed in terms of ACL injuries during 1-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
1
22
0
2
Order By: Relevance
“…Knowing that the effect of an intervention is presumed to decrease as testing moves from efficacy to effectiveness to dissemination and implementation research stages, the results of the current controlled experimental study that was conducted under unenforced real-world implementation conditions can be considered promising. Moreover, in addition to the recent study by Westin et al (2020) who reported a 45% reduction in the ACL injury incidence rate in U18 skiers, this is the first exercise-based prevention study focusing on younger skiers and different types of injuries. Notably, the IG differed from the CG in the average 2-weekly prevalence of traumatic knee injuries, knee overuse injuries, and lower back overuse injuries, three of the major injuryrelated hot spots in youth skiers (Westin et al, 2012;Müller et al, 2017;Fröhlich et al, 2020a,b;Peterhans et al, 2020;Schoeb et al, 2020).…”
Section: The Ispa Int Programme-promising Results Toward Effective In...mentioning
confidence: 91%
See 2 more Smart Citations
“…Knowing that the effect of an intervention is presumed to decrease as testing moves from efficacy to effectiveness to dissemination and implementation research stages, the results of the current controlled experimental study that was conducted under unenforced real-world implementation conditions can be considered promising. Moreover, in addition to the recent study by Westin et al (2020) who reported a 45% reduction in the ACL injury incidence rate in U18 skiers, this is the first exercise-based prevention study focusing on younger skiers and different types of injuries. Notably, the IG differed from the CG in the average 2-weekly prevalence of traumatic knee injuries, knee overuse injuries, and lower back overuse injuries, three of the major injuryrelated hot spots in youth skiers (Westin et al, 2012;Müller et al, 2017;Fröhlich et al, 2020a,b;Peterhans et al, 2020;Schoeb et al, 2020).…”
Section: The Ispa Int Programme-promising Results Toward Effective In...mentioning
confidence: 91%
“…Knowing that the effect of an intervention is presumed to decrease as testing moves from efficacy to effectiveness to dissemination and implementation research stages, the results of the current controlled experimental study that was conducted under unenforced real-world implementation conditions can be considered promising. Moreover, in addition to the recent study by Westin et al (2020) who reported a 45% reduction in the ACL injury incidence rate in U18 skiers, this is the first exercise-based prevention study focusing on younger skiers and different types of injuries.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a study by Schoeb et al ( 35), an off-snow injury prevention program for Swiss aged under 16 years (U16) competitive skiers performed once a week, reduced the 2-weekly prevalence of knee trauma, knee overuse, and lower back overuse complaints. Another study by Westin et al (36) using a neuromuscular prevention program on-and off-snow, showed a reduction of first episode ACL injury in competitive alpine skiers between 16 and 20 years of age. Both these programs were carried out during the whole skiing season.…”
Section: Discussionmentioning
confidence: 95%
“…Physical aspects are indeed known to be a key driver for injury risk in alpine ski racing. [23][24][25][26][27][28][29] Moreover, also in many sports other than alpine ski racing, the benefits of physical fitness-related injury prevention programmes have been demonstrated. [30][31][32] Concerning the 'ski, plate, binding, boot' category, several stakeholders suggested a less aggressive setup as one of the most promising approaches.…”
Section: Potential Change Of Perception Over the Last Decadementioning
confidence: 99%